TESTING MWCNT-COOH/Fe3O4 NANOCOMPOSITE FOR THE REMOVAL OF AMPICILLIN FROM SYNTHETIC AQUEOUS SOLUTIONS - LUNG, Ildiko; STEGARESCU, Adina; OPRIŞ, Ocsana; SORAN, Maria-Loredana (Studia Universitatis Babeș-Bolyai Chemia, 2022)
The aim of this paper consisted of the carbon nanotube nanocomposite testing for the removal of ampicillin from aqueous solutions. To determine the optimum experimental conditions for ampicillin adsorption on nanocomposite, several parameters were selected: the pH, initial concentration of pollutant, adsorbent dose and contact time. The high-performance liquid chromatography was used to determine the residual ampicillin concentration from aqueous solutions. The best removal of the antibiotic on the tested nanocomposite was obtained with an initial concentration of 40 mg L−1 with 1 g L−1, pH 2 in 20 min.